Bibliometric Analysis of Water Resource Development and Utilization Based Research Studies in Sri Lanka - Navaneethakrishnan, S.; Sivakumar, S. (International Journal of Scientific and Engineering Research, 2015)
Sri Lanka’s science and technology research and development activities are now being directed towards facilitating the country’s development process. In this connection main scope of this study is focused on Water Resource Development Studies based publications of Sri Lankan scholars. Studies on evaluation, development and quality of water Water Resource Development Studies based research of Sri Lanka will led to development of new scholarly activities. A total of 1026 records of contributions of 2254 authors with Sri Lankan affiliation were analyzed in this study to identify the research trend of Sri Lankan contributions in water Water Resource Development Studies based research with bibliometric indicators. The analysis of the data reveals that generally there is no progressive increase in Relative growth rate of contributions and Degree of Collaboration was 0.83 during the study span. Among the productive authors Giordano, M. is in the top position and ‘Agricultural Water Management’ was preferred by scholars for scholarly communication.
Keywords: Water research; Bibliometrics